Temporal and spatial variability in the macrozoobenthic community along a salinity gradient in the Castillos Lagoon (Uruguay) - Jorcin, A. (E Schweizerbart'sche Verlags, 1999)
The macrozoobenthic community of the Castillos Lagoon system (East Coast of Uruguay) was sampled during autumn, winter, spring and summer of 1991, in order to describe the community structure and the spatial and temporal patterns of distribution. Eleven sampling stations were distributed along a salinity gradient in a north-south direction (8 replicates were collected at each station). The maximum density of organisms was found at the central part of the lagoon (stations 6 and 7) where the bivalve Erodona mactroides and gastropod Heleobia australis were dominants. No significant correlation between the overall abundance of organisms and salinity could be demonstrated (r = 0.43, p > 0.1). However, a reduction in organism abundance between the autumn and the summer coincided with a marked drop in salinity. Falling levels of dissolved oxygen could have influenced the decreasing density of organisms (r = 0.75, p < 0.05). Species richness and diversity were correlated (p < 0.1) with salinity but the degree of correlation was not uniformly significant between sampling periods.